Turn to me: electrophysiological correlates of frontal vs. averted view face and body processing are associated with trait empathy - Soria Bauser, Denise; Thoma, Patrizia; Suchan, Boris (Frontiers in Integrative Neuroscience, 2012)
The processing of emotional faces and bodies has been associated with brain regions related to empathic responding in interpersonal contexts. The aim of the present Electroencephalography (EEG) study was to investigate differences in the time course underlying the processing of bodies and faces showing neutral, happy, or angry expressions. The P100 and N170 were analyzed in response to the presentation of bodies and faces. Stimuli were presented either from a perspective facing the observer directly or being averted by 45° to manipulate the degree to which the participants had the impression of being involved in a dyadic interpersonal interaction. Participants were instructed to identify the emotional expression (neutral, happy, or angry) by pressing the corresponding button. The result pattern mirrored poorer behavioral performance for averted relative to frontal stimuli. P100 amplitudes were enhanced and latencies shorter for averted relative to frontal bodies, while P100 and N170 components were additionally affected by electrode position and hemisphere for faces. Affective trait empathy correlated with faster recognition of facial emotions and most consistently with higher recognition accuracy and larger N170 amplitudes for angry expressions, while cognitive trait empathy was mostly linked to shorter P100 latencies for averted expressions. The results highlight the contribution of trait empathy to fast and accurate identification of emotional faces and emotional actions conveyed by bodies.